Survei Tingkat Kebugaran Jasmani Siswa Sekolah Sepakbola Iguana Kicker’s Club Kota Batu Usia 14 Tahun - Kurniawan, Dian; Amiq, Fahrial (Universitas Maritim AMNI Semarang, 2025)
Good physical fitness is necessary for everyone. The body's ability to carry out daily activities without experiencing excessive fatigue is known as good physical fitness. The aim of the research was to determine and assess the level of physical fitness of 14 year old Iguana Kickers Club football school students in Batu City. The quantitative descriptive survey method was used in this research. In this research, 14 year old Iguana Kickers Club football school students from Batu City were the subjects. By using the Indonesian Physical Fitness Test instrument for ages 13-15 years and observation as a non-test instrument. Data analysis uses descriptive statistics. The research results showed that of the 28 students surveyed, 2 students with a percentage of 7.14% were in the very good criteria, 4 students with a percentage of 14.28% were in the good criteria, 15 students with a percentage of 53.57% were in the medium criteria, 3 students with a percentage of 10.71% fall into the poor criteria, and 4 students with a percentage of 14.28% fall into the very poor criteria. Based on the research results, it shows that the 14 year old Iguana Kickers Club Batu City students have a moderate level of physical fitness. It is hoped that this research will make students more aware of the importance of maintaining fitness and encourage them to become better.